Twisting measurement and compensation of optical shape sensor based on spun multicore fiber. (June 2020) - Floris, Ignazio; Madrigal, Javier; Sales, Salvador; Calderón, Pedro A.; Adam, Jose M.
Highlights: The accuracy of fiber optic shape sensors is limited by external twisting. The paper presents a novel method for twisting compensation. Experimental tests on spun-MCF-based fiber optic shape sensors. The new results can enhance the accuracy of fiber optic shape sensors. Abstract: This study presents a novel method for twisting compensation in optical shape sensing and first reports on twisting sensing by using Fiber Bragg Gratings (FBG) inscribed in a spun Multicore Fiber (MCF). A simple approach, based on Saint-Venant's Torsion Theory for homogeneous circular cylinders, was developed to calculate the fiber twisting from the longitudinal strain sensed in the cores and reconstruct three-dimensional shape taking into account and compensating the twisting, by enhancing the mathematical formulation of the previous approaches. Then, a 44 mm-long pre-twisted fiber optic shape sensor was produced in the Institute for Telecommunications and Multimedia Applications (iTEAM) of the UPV, by writing four FBGs in a spun multicore fiber (diameter of 125.1 μm) with a pre-twisting of 64.9 rotation/meter. Finally, a series of experiments were performed to validate the method and evaluate the sensor performance. The outcomes of the experiments, perfectly in accordance with the theory, prove the elastic behavior of the sensor, even at high levels of deformation. Moreover, the proposed Spun-MCF-based Shape Sensor resulted able to measure twisting with a sensitivity of 0.23 pm/° and accuracy of 4.81° within a wide dynamic range of ±270° (±6136.4°/m). These new results can notably enhance the accuracy of fiber optic shape sensors and lead to the design of new fiber geometries and sensors.